Influence of tool material on mechanical and microstructural properties of friction stir welded 316L austenitic stainless steel butt joints. (August 2016) - Shashi Kumar, S.; Murugan, N.; Ramachandran, K.K.
Abstract: In the present research, the influence of friction stir welding (FSW) tool material on the mechanical and microstructural properties of friction stir (FS) welded 316L stainless steel butt joints is investigated. FS welds were produced using two different tungsten based FSW tools having identical tool shoulder and pin profiles. In both the cases, the FSW experimental runs were carried out using tool rotational speed of 600 rpm, welding speed of 45 mm/min, axial force of 11 kN and tool tilt angle of 1.5°. The results of the study show that the joints produced using the tungsten lanthanum oxide tool are having superior mechanical and microstructural properties when compared to the joints produced using tungsten heavy alloy tool. Furthermore, the tool degradation study by mass loss and photographic techniques suggests that the tungsten lanthanum oxide tool is more prone to degradation by plastic deformation, whereas the tungsten heavy alloy tool is more prone to degradation by wear. Highlights: The effect of two different tungsten based FSW tool materials on the joint characteristics is investigated. The studies show that the tool material plays a significant role in the performance of the joints. The tool wear and deformation affect the mechanical and microstructural characteristics of the joints. Among the two FSW tool materials, the tungsten lanthanum oxide is superior over the tungsten heavy alloy tool.